Cytochrome P450 1A1 (CYP1A1) protects against nonalcoholic fatty liver disease caused by Western diet containing benzo[a]pyrene in mice. (March 2018) - Uno, Shigeyuki; Nebert, Daniel W.; Makishima, Makoto
Abstract: The Western diet contributes to nonalcoholic fatty liver disease (NAFLD) pathogenesis. Benzo[ a ]pyrene (BaP), a prototypical environmental pollutant produced by combustion processes, is present in charcoal-grilled meat. Cytochrome P450 1A1 (CYP1A1) metabolizes BaP, resulting in either detoxication or metabolic activation in a context-dependent manner. To elucidate a role of CYP1A1-BaP in NAFLD pathogenesis, we compared the effects of a Western diet, with or without oral BaP treatment, on the development of NAFLD in Cyp1a1 (−/−) mice versus wild-type mice. A Western diet plus BaP induced lipid-droplet accumulation in liver of Cyp1a1 (−/−) mice, but not wild-type mice. The hepatic steatosis observed in Cyp1a1 (−/−) mice was associated with increased cholesterol, triglyceride and bile acid levels. Cyp1a1 (−/−) mice fed Western diet plus BaP had changes in expression of genes involved in bile acid and lipid metabolism, and showed no increase in Cyp1a2 expression but did exhibit enhanced Cyp1b1 mRNA expression, as well as hepatic inflammation. Enhanced BaP metabolic activation, oxidative stress and inflammation may exacerbate metabolic dysfunction in liver of Cyp1a1 (−/−) mice. Thus, Western diet plus BaP induces NAFLD and hepatic inflammation in Cyp1a1 (−/−) mice in comparison to wild-type mice, indicating a protective role of CYP1A1 against NAFLD pathogenesis. Highlights: A Western diet with benzo[ a ]pyrene induces hepatic steatosis in Cyp1a1 (−/−) mice. Hepatic steatosis in these mice is associated with lipid and bile acid accumulation. Bile acid export and lipid metabolism gene expression is dysregulated in these mice. These mice also have hepatic inflammation, likely due to enhanced benzo[ a ]pyrene toxicity. CYP1A1 protects against nonalcoholic fatty liver disease induced by benzo[ a ]pyrene.